72a-96-48=

Simple and best practice solution for 72a-96-48= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 72a-96-48= equation:


72a-96-48=0

We simplify the equation to the form, which is simple to understand
72a-96-48=0

We move all terms containing a to the left and all other terms to the right.
+72a=0+96+48

We simplify left and right side of the equation.
+72a=+144

We divide both sides of the equation by 72 to get a.
a=2

See similar equations:

| -4n+2(n-6)+8=10 | | 2x+16y=104 | | 4(x+6)=9-2x | | 200x+96-120= | | 20x+54.1=-45.9 | | -6-x=9+4x | | 75-15= | | 3k+4(k-3)+10=-58 | | -6x+3(x+9)-12=27 | | -3t+2(t-2)+6=-3 | | -9+5n+7= | | 2r+8-5= | | -2m-5-2(m-2)=3m-(4m-6)-5m+1 | | 2n+2(n+7)+1=39 | | 2y+2(y+1)=-6 | | 85+55x=y | | y=120+16(x) | | 2-6=a+a+4 | | -4p-3(4-3p)=2(p-4)-22 | | 3r+5(r-1)=27 | | 5(x+3)=8(x+6) | | 14x+12=4x^2 | | 4(r+6)=-49 | | -8x+48=-2(x-2)(x-2)+32 | | X+-1=0 | | -3(r+7)=-40 | | X+-2=0 | | 10(v+2)-2v=2(4v+3)-9 | | 2.87x+25.83=51.66 | | 5r^2=48+r | | -4(r+3)=-61 | | -10x+4=-7x+13 |

Equations solver categories